Pengaruh Literasi Keuangan, Sikap Keuangan dan Gaya Hidup Terhadap Pengelolaan Keuangan UMKM - Putri, Mayzura Rahma Aulia; Putri, Sofie Yunida (Forum Kerjasama Pendidikan Tinggi, 2024)
The study aims to analyze the effect of financial literacy, attitudes and lifestyle on the financial management of MSMEs. This research employs quantitative research methodology, collecting data by the distribution of questionnaires to all participants via offline and online means. The research location is in Karang Pilang District, Surabaya. The selected population is all MSMEs in Karang Pilang District. Using the simple random sampling procedure, 78 MSMEs were selected as research samples. The data was processed using SmartPLS software with PLS-SEM data analysis techniques. The outcomes demonstrated that financial literacy has no affect on the financial management of MSMEs.. In contrast, financial attitudes have a positive effect on MSME financial management and lifestyle has a positive effect on MSME financial management. This research provides valuable insights for the development of MSME empowerment strategies, particularly with regard to financial management. The findings can be applied as a a basis for designing more effective training and mentoring activities, with a focus on improving appropriate financial attitudes and prudent lifestyles among MSME actors.